2004
DOI: 10.1371/journal.pbio.0020365
|View full text |Cite
|
Sign up to set email alerts
|

Representation of Attended Versus Remembered Locations in Prefrontal Cortex

Abstract: A great deal of research on the prefrontal cortex (PF), especially in nonhuman primates, has focused on the theory that it functions predominantly in the maintenance of short-term memories, and neurophysiologists have often interpreted PF's delay-period activity in the context of this theory. Neuroimaging results, however, suggest that PF's function extends beyond the maintenance of memories to include aspects of attention, such as the monitoring and selection of information. To explore alternative interpretat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
179
4
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(202 citation statements)
references
References 99 publications
17
179
4
1
Order By: Relevance
“…There is no working memory requirement. Thus, the present results, like the findings from several ablation (Bussey et al, 2001;Rushworth et al, 1997) and physiological (Lebedev et al, 2004;Passingham and Sakai, 2004) studies, argue against the idea that the primary function of the prefrontal cortex is the mediation of working memory. Instead, the deficit after PFo lesions must be in another domain.…”
Section: Role Of the Pfo In Response Selectioncontrasting
confidence: 55%
“…There is no working memory requirement. Thus, the present results, like the findings from several ablation (Bussey et al, 2001;Rushworth et al, 1997) and physiological (Lebedev et al, 2004;Passingham and Sakai, 2004) studies, argue against the idea that the primary function of the prefrontal cortex is the mediation of working memory. Instead, the deficit after PFo lesions must be in another domain.…”
Section: Role Of the Pfo In Response Selectioncontrasting
confidence: 55%
“…Lesion and single-cell data (Lebedev et al, 2004;Rushworth et al, 2004) suggest the same is true in the macaque, in which the UF has been shown to mediate these functions (Gutnikov et al, 1997).…”
Section: Discussionmentioning
confidence: 87%
“…In fact, an executive function (including working memory) can be thought of as a special case of attentional phenomena (Barkley, 2001) and, conversely, attention can be seen as "a varying reflection, in behavior, of the operation of a single underlying mechanism of cognitive control" (Miller and Cohen, 2001). Various dimensions of attentional control and selection have been put forward as the main functions of the PFC (Rowe and Passingham, 2001;Lebedev et al, 2004).…”
Section: Discussionmentioning
confidence: 99%